A photometrically and spectroscopically confirmed population of passive spiral galaxies - Fraser-McKelvie, Amelia; Brown, Michael J. I.; Pimbblet, Kevin A.; Dolley, Tim; Crossett, Jacob P.; Bonne, Nicolas J. (Monthly notices of the Royal Astronomical Society: Letters, 2016)
We have identified a population of passive spiral galaxies from photometry and integral field spectroscopy. We selected z < 0.035 spiral galaxies that have WISE colours consistent with little mid-infrared emission from warm dust. Matched aperture photometry of 51 spiral galaxies in ultraviolet, optical and mid-infrared show these galaxies have colours consistent with passive galaxies. Six galaxies form a spectroscopic pilot study and were observed using the Wide-Field Spectrograph to check for signs of nebular emission from star formation. We see no evidence of substantial nebular emission found in previous red spiral samples. These six galaxies possess absorption-line spectra with 4000 Å breaks consistent with an average luminosity-weighted age of 2.3 Gyr. Our photometric and integral field spectroscopic observations confirm the existence of a population of local passive spiral galaxies, implying that transformation into early-type morphologies is not required for the quenching of star formation.
Keywords: Galaxies : evolution; Galaxies : general; Galaxies : stellar content; Galaxies : spiral